Inflammatory ER stress responses dictate the immunopathogenic progression of systemic candidiasis - Deepika Awasthi; Sahil Chopra; Byuri A. Cho; Alexander Emmanuelli; Tito A. Sandoval; Sung-Min Hwang; Chang-Suk Chae; Camilla Salvagno; Chen Tan; Liliana Vasquez-Urbina; Jose J. Fernandez Rodriguez; Sara F. Santagostino; et al. (The Journal of Clinical Investigation, 2023)
Recognition of pathogen-associated molecular patterns can trigger the inositol-requiring enzyme 1 α (IRE1α) arm of the endoplasmic reticulum (ER) stress response in innate immune cells. This process maintains ER homeostasis and also coordinates diverse immunomodulatory programs during bacterial and viral infections. However, the role of innate IRE1α signaling in response to fungal pathogens remains elusive. Here, we report that systemic infection with the human opportunistic fungal pathogen Candida albicans induced proinflammatory IRE1α hyperactivation in myeloid cells that led to fatal kidney immunopathology. Mechanistically, simultaneous activation of the TLR/IL-1R adaptor protein MyD88 and the C-type lectin receptor dectin-1 by C. albicans induced NADPH oxidase–driven generation of ROS, which caused ER stress and IRE1α-dependent overexpression of key inflammatory mediators such as IL-1β, IL-6, chemokine (C-C motif) ligand 5 (CCL5), prostaglandin E2 (PGE2), and TNF-α. Selective ablation of IRE1α in leukocytes, or treatment with an IRE1α pharmacological inhibitor, mitigated kidney inflammation and prolonged the survival of mice with systemic C. albicans infection. Therefore, controlling IRE1α hyperactivation may be useful for impeding the immunopathogenic progression of disseminated candidiasis.